“Liquid biopsy” - extracellular vesicles as potential novel players towards precision medicine in asthma - Ambrożej, Dominika; Stelmaszczyk-Emmel, Anna; Czystowska-Kuźmicz, Małgorzata; Feleszko, Wojciech (Frontiers in Immunology, 2022)
Extracellular vesicles (EVs) have emerged as vital mediators in intracellular communication in the lung microenvironment. Environmental exposure to various triggers (e.g., viruses, allergens) stimulates the EV-mediated cascade of pro-inflammatory responses that play a key role in the asthma pathomechanism. This complex EV-mediated crosstalk in the asthmatic lung microenvironment occurs between different cell types, including airway epithelial cells and immune cells. The cargo composition of EVs mirrors hereby the type and activation status of the parent cell. Therefore, EVs collected in a noninvasive way (e.g., in nasal lavage, serum) could inform on the disease status as a “liquid biopsy”, which is particularly important in the pediatric population. As a heterogeneous disease, asthma with its distinct endotypes and phenotypes requires more investigation to develop novel diagnostics and personalized case management. Filling these knowledge gaps may be facilitated by further EV research. Here, we summarize the contribution of EVs in the lung microenvironment as potential novel players towards precision medicine in the development of asthma. Although rapidly evolving, the EV field is still in its infancy. However, it is expected that a better understanding of the role of EVs in the asthma pathomechanism will open up new horizons for precision medicine diagnostic and therapeutic solutions.